Effect of Dye Localization and Self-Interactions on the Photosensitized Generation of Singlet Oxygen by Rose Bengal Bound to Bovine Serum Albumin - Lissi-Gervaso, E; Aspee-Lamas, A (Elsevier, 2014)
The spectroscopic and photophysical properties of rose bengal (RB) encased in bovine serum albumin (BSA) have been examined to evaluate the photosensitized generation of singlet molecular oxygen (1O2). The results show that RB photophysical and photosensitizing properties are highly modulated by the average number of dye molecules per protein (n). At n ?1, the dye molecule is tightly located into the hydrophobic nanocavity site I of the BSA molecule with a binding constant Kb = 0.15 ± 0.01 ?M-1. The interaction with surrounding amino acids induces heterogeneous decay of both singlet and triplet excited states of RB and partially reduce its triplet quantum yield as compared with that in buffer solution. However, despite of the diffusive barrier imposed by the protein nanocavity to 3O2, the quenching of 3RBBSA generates 1O2 with quantum yield ?? = 0.35 ± 0.05. In turns, the intraprotein generated 1O2 is able to diffuse through the bulk solution, where is dynamically quenched by BSA itself with an overall quenching rate constant of 7.3 × 108 M-1 s-1. However, at n > 1, nonspecific binding of up to ?6 RB molecules per BSA is produced, allowing efficient static quenching of excited states of RB preventing photosensitization of 1O2. These results provide useful information for development of dye-protein adducts suitable for using as potential intracellular photosensitizers. © 2014 Elsevier Ltd. All rights reserved.